IMPLEMENTASI KEBIJAKAN PENGENDALIAN MENARA BERSAMA DALAM PENINGKATAN PENDAPATAN ASLI DAERAH - Arnanda, Adhitia (Jurnal Ilmu Administrasi Negara, 2016)
Tower Control Policy Implementation Together In The increase in local revenue. Key informant was Head of Transportation and Communication Equipment Siak, Head of Infocom, Section Head of Post and Telecommunications, owner Tower (Provider) and society. Data collection technique used observation, interview and documentation. Data analysis method used is descriptive qualitative analysis with interactive data analysis model. The results showed that the policy evaluation arrangement telecommunications tower together in the Siak need to be re-examined in view of the Regional Regulation Siak District No. 20 of 2011 on Levy Control Tower is not set out clear and detailed about the magnitude of the amount and the fees to be paid by the provider at the time of payment development levy tower/tower, because the regulation only governs the types of charges from the licensing of telecommunications towers.